Three-phase dry-type distribution transformers 50 Hz, from 100 to 2500 kVA with highest voltage for equipment not exceeding 36 kV. General requirements and requirements for transformers with highest voltage for equipment not exceeding 24 kV Part 1, (15th August 1996) - British Standards Institution
No abstract available